Nonlinear main components of the cytokine profile in children with community-acquired pneumonia - N. V. Iziurova; D. Yu. Nokhrin; A. Yu. Savochkina; A. N. Uzunova (Медицинская иммунология, 2024)
Cytokines are the key mediators which control and regulate immune and inflammatory responses via complex networks and serve as biomarkers of many diseases. Quantitative determination of cytokines is helpful in assessing immune status and adjusting therapy for various inflammatory diseases, such as sepsis and pneumonia. Since community-acquired pneumonia remains a common cause of childhood morbidity and mortality. At the present stage, prognosis of the disease severity in children is an urgent problem. The aim of our study was to identify associations between cytokine levels in healthy children and in children with community-acquired pneumonia (CAP), depending on the age of patients and severity of the pathological process. The work was carried out at the Department of Microbiology, Virology and Immunology, Department of Propaedeutics of Childhood Diseases and Pediatrics, and at the Research Institute of Immunology at the South Ural State Medical University. The study included 117 children aged 1 to 18 years with radiologically confirmed diagnosis of CAP, either severe or mild degree. The comparison group was composed from 28 healthy children who did not have community-acquired pneumonia, as well as other signs of acute respiratory viral infection at the time of examination, being observed for any chronic disorders. The levels of IL-1β, IFNγ, IL-6, IL-4, IL-10, IL-2, TNFα, IFNλ2 (IL-28A), IFNλ3 (IL-28B), IL-8, MCP-1, IL-17AF, GM-CSF were determined in blood serum by means of ELISA test systems (a “sandwich” technique with peroxidase as an indicator enzyme). For statistical analysis, a multidimensional method was used, i.e., non-linear analysis of the principal components using the CATPCA algorithm. Among the children with CAP, our study revealed a consistent increase of IL-1ß, IL-4, IL-10, IL-2, TNFα, IFNλ2 (IL-28A), IFNλ3 (IL-28B), IL-8, MCP-1, IL-17AF, GM-CSF in blood serum. The highest correlation with severity was shown for IFNλ2 (IL-28A), IFNλ3 (IL-28B) and MCP-1, which may be considered additional biomarkers of the CAP severity. There was also a significant variability of the cytokine profile in healthy children and its significant skewing in pneumonia, especially in severe cases.